2005
DOI: 10.1038/nature03499
|View full text |Cite
|
Sign up to set email alerts
|

Active out-of-sequence thrust faulting in the central Nepalese Himalaya

Abstract: Recent convergence between India and Eurasia is commonly assumed to be accommodated mainly along a single fault--the Main Himalayan Thrust (MHT)--which reaches the surface in the Siwalik Hills of southern Nepal. Although this model is consistent with geodetic, geomorphic and microseismic data, an alternative model incorporating slip on more northerly surface faults has been proposed to be consistent with these data as well. Here we present in situ cosmogenic 10Be data indicating a fourfold increase in millenni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
224
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(237 citation statements)
references
References 26 publications
13
224
0
Order By: Relevance
“…Erosion and uplift are two basic geological processes associated with mountain building, and there has been an upsurge of interests in better understanding the complex and dynamic feedbacks between tectonics, climate, and denudation (i.e., Wobus et al 2005). However the exact relationships and interactions between erosion and uplift are often difficult to quantify due to the lack of observable or measurable data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Erosion and uplift are two basic geological processes associated with mountain building, and there has been an upsurge of interests in better understanding the complex and dynamic feedbacks between tectonics, climate, and denudation (i.e., Wobus et al 2005). However the exact relationships and interactions between erosion and uplift are often difficult to quantify due to the lack of observable or measurable data.…”
Section: Introductionmentioning
confidence: 99%
“…Riebe et al (2000) studied the erosion rates in the Sierra Nevada of California using cosmogenic 26 Al and 10 Be, while in the same region, Cecil et al (2006) studied the Cenozoic exhumation from (U -Th) / He thermochronology. Wobus et al (2005) suggested from 10 Be data that a locus of active deformation well to the north of the Himalayan deformation front has been maintained by dynamic interactions between climate, erosion and tectonics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a lot of work has been done regarding the evolution of river terraces and their neo-tectonic and climatic implications (Burbank, 2005;Wobus et al, 2005). Due to lack of suitable organic material and limited upper bound (<50 ka) for 14 C dating technique, OSL dating technique was explored due to ubiquitous dating material (Quartz and Feldspar) and expanded upper age limit up to 200-300 ka.…”
Section: Introductionmentioning
confidence: 99%
“…The Himalaya is an active south propagating foldthrust-belt as a result of collision between Indian and Asian plates and preserves signatures of past tectonic and climatic events in the form of various geomorphic archives (Bilham et al, 1997;Senthil et al, 2001;Hodges et al, 2004;Pratt et al, 2004;Burbank, 2005;Wobus et al, 2005). Most of the projects in the Indian Himalayas focused on Lake Sequences for palaeo-climate and neotectonic studies (Singhvi et al, 1994;Banerjee et al 1999;Chamyal and Juyal, 2005), which can be dated by 14 C and less attention was paid to fluvial sediments in the Himalayan river Valleys.…”
Section: Introductionmentioning
confidence: 99%